Growing edible sweet bamboo - Thakur, Ajay; Chauhan, J MS; Yadav, Shambhavi (Indian Horticulture, 2019)
The sweet bamboo (Dendrocalamus asper) is a fast-growing species, which produces quality bamboo shoots as well as good biomass. This bamboo is highly amenable to tissue culture and is being cultivated in India. Edible shoots become ready within 5-6 weeks from emergence and harvested during the rainy season (June-October). Peeled shoots weigh 3-5 kg. Apart from edible shoots, this bamboo is an excellent industrial raw material. Micro-propagation is the best way to mass multiply this bamboo as seed production takes long time and other methods of vegetative propagation are comparatively slow. Shoot production starts 5 years after plantation which increases gradually.